Structure and Dynamics of the Gut Bacterial Community Across the Developmental Stages of the Coffee Berry Borer, Hypothenemus hampei - Mejía-Alvarado, Fernan Santiago; Ghneim-Herrera, Thaura; Góngora, Carmenza E.; Benavides, Pablo; Navarro-Escalante, Lucio (Frontiers in Microbiology, 2021)
The coffee berry borer (CBB); Hypothenemus hampei (Coleoptera: Curculionidae), is widely recognized as the major insect pest of coffee crops. Like many other arthropods, CBB harbors numerous bacteria species that may have important physiological roles in host nutrition, detoxification, immunity and protection. To date, the structure and dynamics of the gut-associated bacterial community across the CBB life cycle is not yet well understood. A better understanding of the complex relationship between CBB and its bacterial companions may provide new opportunities for insect control. In the current investigation, we analyzed the diversity and abundance of gut microbiota across the CBB developmental stages under field conditions by using high-throughput Illumina sequencing of the 16S ribosomal RNA gene. Overall, 12 bacterial phyla, 33 classes, 47 orders, 80 families and 147 genera were identified across all life stages, including egg, larva 1, larva 2, pupa and adults (female and male). Proteobacteria and Firmicutes phyla dominated the microbiota along the entire insect life cycle. Among the 147 genera, the 10 most abundant were members of Ochrobactrum (15.6%), Pantoea (6.6%), Erwinia (5.8%), Lactobacillus (4.5%), Acinetobacter (3.6%), Stenotrophomonas (3.2%), Akkermansia (3.1%), Agrobacterium (3%), Curtobacterium (2.8%), and Clostridium (2.7%). We found that the overall bacterial diversity and community composition do not change across life stages, which correlates with the uniformity of food source throughout the entire insect life cycle within the coffee bean. A large proportion of the identified OTUs (73.4%) were shared across all life stages, including members of genera Pantoea, Erwinia, Agrobacterium, Ochrobactrum, Pseudomonas, Acinetobacter, Brachybacterium, Sphingomonas and Methylobacterium, which can be considered as the gut-associated core microbiota of H. hampei. Our findings bring additional data to enrich the understanding of gut microbiota in CBB and its possible use for development of insect control strategies.